2011
DOI: 10.1002/mus.21924
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of plasmapheresis in myasthenia gravis: Delayed therapy is not favorable

Abstract: Delaying PLEX therapy for MG by more than 2 days after admission may lead to higher mortality and complication rates, and thus prompt therapy is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 28 publications
(28 reference statements)
3
20
0
1
Order By: Relevance
“…A potential limitation to the use of TPE is delay in starting therapy while waiting for CVC placement, which has been reported to increase the risk of complications 30. Congruent with a previous report, we found no significant delays in initiating TPE among patients who needed a CVC and no difference in the time to start TPE in patients with or without central lines 15…”
Section: Discussionsupporting
confidence: 71%
“…A potential limitation to the use of TPE is delay in starting therapy while waiting for CVC placement, which has been reported to increase the risk of complications 30. Congruent with a previous report, we found no significant delays in initiating TPE among patients who needed a CVC and no difference in the time to start TPE in patients with or without central lines 15…”
Section: Discussionsupporting
confidence: 71%
“…Given this rapid response, PLEX may be the preferred treatment in situations such as threatening myasthenic crisis. In such situations, PLEX should be provided within 2 days to limit mortality and decrease the complication rate of treatment …”
mentioning
confidence: 99%
“…In such situations, PLEX should be provided within 2 days to limit mortality and decrease the complication rate of treatment. 11 Although most reports have indicated that PLEX is a safe treatment with few side effects in MG patients, 3,12 including the elderly, 13 it is perceived to be a complex treatment that is difficult to prescribe, requires vascular access by central lines, and requires hospital admission. It has been suggested that MG patients who are elderly or have complex comorbid diseases might have better outcomes if IVIg is used rather than PLEX.…”
mentioning
confidence: 99%
“…[21][22][23] Randomized clinical studies carried out in adult populations comparing the efficacies of PLEX and IVIG demonstrate that they are generally comparable, with similar efficacies, durations of benefit, and safety profiles. 11,[24][25][26][27][28] While the effectiveness of PLEX and IVIG has been established in adult studies, our study is the first attempt to compare the role of PLEX vs IVIG as maintenance therapies for juvenile MG. In our study, we found significant differences in both objective and subjective improvements at follow-up clinic visits in the children with generalized juvenile MG who received PLEX vs IVIG vs combined treatments.…”
Section: Discussionmentioning
confidence: 99%